Educational Policy: Voices from Local English Teachers and Students towards National Exam in Yogyakarta - Laser Romios; Nindya Primandita; Novilda Angela Saragih (English Education Study Program, Faculty of Education and Teachers Training, Tidar Univer, 2020)
This study is aimed at exploring the voices of English teachers and students of a state senior high school towards the National Exam policy and its implementation in Indonesia. Several theories of psychology and language learning were applied in this study as the theoretical framework. This study used a descriptive qualitative method. The participants were chosen by purposive sampling technique. The data for this study were garnered through a Focus Group Discussion (FGD) conducted to the selected twelfth-grade students and semi-structured interviews done to two English teachers. Both data were analyzed descriptively. Upon the analysis, two paramount themes prevailed: (1) the negative response towards the implementation and accuracy of National Exam (NE) policy in Indonesia; and (2) unintended impacts of NE policy on teaching and learning activity, students’ motivation, and English Language Learning and Curriculum. This study offers information for the government as the policymaker, school leaders, teachers, and researchers to understand how the NE is implemented at the school level.